2023
DOI: 10.1249/mss.0000000000003281
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Anterior Cruciate Ligament Tears in National Collegiate Athletic Association Athletes: 2014/15 – 2018/19

Derek R. Dewig,
Adrian J. Boltz,
Reagan E. Moffit
et al.

Abstract: Anterior cruciate ligament (ACL) tears are prevalent in National Collegiate Athletic Association (NCAA) sports, and updated epidemiological evidence is needed to adequately inform prevention efforts. Purpose To describe the epidemiology of ACL tears in NCAA men’s and women’s sports. Methods Injury and exposure data collected within the NCAA Injury Surveillance Program from 2014/15-2018/19 were analyzed. ACL tear frequencies, rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A significant limitation of this study was selection bias: one can speculate that participants were much more likely to respond to the survey if they had suffered a previous knee injury. This explains the disproportionately high prevalence of knee injuries (42%) within our participant pool, which is significantly higher than previously reported [28]. One would need to sample this population more randomly to better assess the prevalence of STKIs in this population.…”
Section: Discussionmentioning
confidence: 77%
“…A significant limitation of this study was selection bias: one can speculate that participants were much more likely to respond to the survey if they had suffered a previous knee injury. This explains the disproportionately high prevalence of knee injuries (42%) within our participant pool, which is significantly higher than previously reported [28]. One would need to sample this population more randomly to better assess the prevalence of STKIs in this population.…”
Section: Discussionmentioning
confidence: 77%
“…Despite advancements in ACL reconstruction and rehabilitation, research suggests that only a small percentage of athletes are able to return to their pre-injury performance levels (DEWIG, 2023). Long-term consequences such as osteoarthritis are also significant considerations when planning the treatment and rehabilitation of athletes post-ACL injury (DEWIG, 2023). These findings underscore the importance of comprehensive care and ongoing support for athletes undergoing ACL reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…A survey of the Women's Bundesliga also found that the highest prevalence of injuries among female soccer players were in the knee (31%), ankle (22.1%), thigh (12.9%), and head (7.1%) [17]. And among knee injuries, Chandran et al's [18] study of NCAA women's soccer team athletes published in 2023 further found the injury with the highest prevalence in female athletes to be ACL injuries (IR = 2.60 per 10,000 AE).…”
Section: Injuries In Soccermentioning
confidence: 97%